Memperkokoh posisi Departemen Kesehatan dalam sektor kesehatan publik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
There have been many dissappointed tendencies that health services are currently biased to the more wealthy groups in the society. Corporatisms, competitions, and the emanation of more profit-oriented health institutions have put aside the public health service for the poor. Unfortunately, even the Department of Health have failed to stand for its fundamental functions in maintaining the public health and protecting the unfortunate people. The Department have been unable to respond the competitive environment and prevent the brain drain of qualified doctors from the public hospitals to the private institutions. It is suggested that the Department of Health should reorient its mission and tasks by applying strategic management approach. This new approach should also be accompanied with stronger external control of the public through the parliament and other pressure group